2011
DOI: 10.1186/ar3274
|View full text |Cite
|
Sign up to set email alerts
|

The tumour-associated glycoprotein podoplanin is expressed in fibroblast-like synoviocytes of the hyperplastic synovial lining layer in rheumatoid arthritis

Abstract: IntroductionActivated fibroblast-like synoviocytes (FLSs) in rheumatoid arthritis (RA) share many characteristics with tumour cells and are key mediators of synovial tissue transformation and joint destruction. The glycoprotein podoplanin is upregulated in the invasive front of several human cancers and has been associated with epithelial-mesenchymal transition, increased cell migration and tissue invasion. The aim of this study was to investigate whether podoplanin is expressed in areas of synovial transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 45 publications
4
93
1
Order By: Relevance
“…29e32 Synovial fibroblasts in the joints of rheumatoid arthritis patients also display Pdpn, suggesting that this transition accompanies inflammation. 67,68 Herein, we demonstrate that fibroblasts in vitro can transition in response to inflammatory stimuli that have NF-kB activation as a common element and, likewise, as noted in an acute mouse ear model of inflammation, Tolllike receptor and interferon signaling pathways did not contribute to Pdpn induction. 66 Pdpn is constitutively expressed in lymphoid reticular stroma; however, when the lymph node becomes reactive or effectively inflamed, Pdpn levels increase even further.…”
Section: Discussionmentioning
confidence: 50%
“…29e32 Synovial fibroblasts in the joints of rheumatoid arthritis patients also display Pdpn, suggesting that this transition accompanies inflammation. 67,68 Herein, we demonstrate that fibroblasts in vitro can transition in response to inflammatory stimuli that have NF-kB activation as a common element and, likewise, as noted in an acute mouse ear model of inflammation, Tolllike receptor and interferon signaling pathways did not contribute to Pdpn induction. 66 Pdpn is constitutively expressed in lymphoid reticular stroma; however, when the lymph node becomes reactive or effectively inflamed, Pdpn levels increase even further.…”
Section: Discussionmentioning
confidence: 50%
“…These authors showed induction of podoplanin by treatment 14 -mechanism involving the induction of the IL-3 receptor. In an interesting report , Ekwall et al (2011) showed that podoplanin is up-regulated in patients with rheumatoid arthritis, but not in patients with osteoarthritis. In another report, were shown to induce podoplanin expression; however only IL-7 was able to induce also Prox1, and to stimulate endothelial cell growth (Al-Rawi et al, 2005).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Immunofluorescence and Confocal Microscopy-Human synovial tissue specimens from five RA patients were processed for immunohistochemical staining as described previously (45). In brief, paraformaldehyde-fixed paraffin-embedded 4-m sections of human synovial tissue were deparaffinized and rehydrated and subjected to an antigen retrieval procedure.…”
Section: Methodsmentioning
confidence: 99%